Karakterisasi Ketangguhan Impak Paduan Aluminium–Seng Daur Ulang Hasil Pengecoran Menggunakan Metode Charpy - Jagodang Harahap; Indra Mawardi; Sumardi Sumardi; Andi Sudirman; Arya Rudi Nasution (Rekayasa Material, Manufaktur dan Energi, 2026)
ABSTRACKThis study aims to evaluate the effect of zinc scrzp additional on the impact toughness of cast aluminum alloys. The composition variations used include 95% aluminum–5% zinc, 85% aluminum–15% zinc, and 70% aluminum–30% zinc. Impact properties were tested using the Charpy method according to ASTM E23 standards, while the fracture surface characteristics were analyzed macroscopically to determine the material failure mechanism. The results showed that increasing zinc scrap content was followed by an increase in the alloy's ability to absorb impact energy. The impact energy values were 1.97 J, 2.24 J, and 3.80 J, respectively, while the impact price increased from 24,625 J/m² to 28,041.7 J/m² and reached 47,500 J/m² at the 70% aluminum–30% zinc composition. Macroscopic observations show that all specimens have brittle fracture characteristics, but differences in alloy compositions cause changes in fracture surface characteristics that correlate with increased impact toughness. Based on these results, it can be concluded that the addition of scrap zinc up to 30% can increase the impact toughness of scrap aluminum alloys from castings, so that they have the potential to be used as an alternative recycled-based material for applications requiring resistance to shock loadsKeywords: Scrap Aluminium, Scap Zinc,Alumnium-Zinc Allow Casting, Charpy Impact